(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2024)
This research addresses the problems of conventional orthoimages created from aerial imagery of urban areas, especially relief displacements, occlusions and information loss caused by man-made objects. An approach is presented to generate more accurate orthoimages based on elevation models that exactly describe the entire surface of the observed region. The approach utilizes the digital building model, in addition to the digital terrain model, in the orthorectification process. Occluded areas are identified and filled in the final orthoimage by merging data from conjugate images. The data used in the research consists of a small block of high resolution aerial images covering an urban area. The images are captured recently with the digital aerial camera UltraCam-D. The image pixel size is 9 m by 9 m yielding a nearly 10-cm ground sample distance. The results reached by applying the proposed approach on the test images have been promising. They have proven the validity of the approach in generating more proper orthoimages.